Quality of life in institutionalized elderly undergoing an active aging program - Magalhães, Carlos (2017)
Introduction: Living with quality is a growing concern of the old population. There is an increasing institutionalization of the elderly, and it is in this context that active aging programs assume relevance, allowing the elderly the contact with experiences that allow them to age with quality of life, by maintaining their autonomy and promoting their physical, mental and emotional well-being. Objective: To evaluate the quality of life (QOL) of institutionalized elderly undergoing to an active aging program. Methods: We have developed a quantitative type study, semi-experimental, in which the following instruments were used to measure the quality of life: EUROHIS-QOL-8 and WHOQOL-OLD, to which sociodemographic and clinical questions were added. Assessments were made in two different moments, before and after the intervention program, in a sample of 37 institutionalized elderly. Results: Concerning the assessment of quality of life related to health (EUROHIS-QOL-8), significant higher scores were obtained in the second moment (p=0.004). Regarding the quality of life (WHOQOL-OLD) related to the elderly significant better scores were also obtained in the second assessment (p=0.001). Conclusions: The results show an improvement in the perception of quality of life in elderly patients undergoing to an active aging program, emphasizing the importance of it.